INTEGRASI PERAN PENDIDIKAN TINGGI DALAM PENGUATAN SEKTOR UMKM - Rousdy Safari Tamba (Majalah Ilmiah Bijak, 2017)
Education has high correlation on economic growth of a country .An increase in linkage higher education against small and medium businesses Micro, Small, Medium Enterprises , with tri dharma college , can be manifested in the strategic plan ( Renstra ) college , in the form of  ( 1 ) forming a network cooperation with Micro, Small, Medium Enterprises ; ( 2 ) Implementing activities road show cooperation with Micro, Small, Medium Enterprises; ( 3 ) to develop a comprehensive internship program based on project approach; and ( 4 ) the development of brand equity and exposure of institutional with the involvement of an agency in the professional activities through strengthening strategic functions and institutions for the laboratory study.